Changes in the development of selected street blocks in peripheral housing estates of Wroclaw - Klincewicz, Patrycja; Szmytkie, Robert (Przestrzenny wymiar badań dziedzictwa kulturowego: Studia z Geografii Politycznej i Historycznej 2020. T. 9-10, 2021)
This work concerns the changes in the development of street blocks located on the peripheral districts of Wroclaw (areas of former villages incorporated into the city boundaries in the 20th century). Presented chapter uses the cartographic method of the city plan analysis and the concept of the urban cycle proposed by M.R.G. Conzen. The analysis was carried out on the basis of case studies which constituted 33 street blocks representative for three morphological periods with different development conditions (the interwar period, the years 1945–1989 and the period after 1989). The subject of the research was: the size of plots and street blocks, the method of dividing the block into plots, the degree of filling the blocks with buildings and the type of development.